Normative Konstituenzien der Demokratie (De Gruyter, 2024)
Democracies are coming under increasing pressure. In the process, the meaning of democracy itself has become the subject of debate. What normative conditions are essential for democracy? And how can we better realize these conditions? This volume brings together responses from relevant representatives of philosophy, political science, and law.